(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective: This study was aimed to assess the knowledge, attitude, and practices (KAP) of the healthcare professionalsin respect to pharmacovigilance and to compare the KAP of resident doctors with KAP of staff nurses. The secondary objective of this study was to further compare the results of various other studies done till dateacross India so as to assessthe major contributors responsible for under reporting. Materials and Methods:This is a cross-sectional, questionnaire-based study; carried out on 70 resident doctors and 71 staff nurses of Hakeem Abdul Hakeem Centenary Hospital, Jamia Hamdard, New Delhi. The questionnaire was designed to assess the KAP regarding pharmacovigilance among the healthcare professionals. Statistical analysis was done using student t- test and Pearson correlation. Results:Our study showed a considerable gap between the adverse event experienced (82.26%) and adverse event reported (39.71%) by the healthcare professionals. From the result of the study it is clearly evident that the resident doctors have unquestionably more knowledge of pharmacovigilance (67.71%) when compared to the nurses (49.85%). How so ever, the nurses showed a better attitude towards the reporting of adverse events (80.12%) and significantly far better in practices (60.71%)regarding pharmacovigilance. It has also been seen there is a significant positive correlation betweenpharmacovigilance training and adverse event reporting.Also healthcare professionals believe that regular workshops and continuing medical education (CMEs) would definitelyimprovethe reporting culture of adverse event among them. Conclusion:From the present study, we concluded that there is a considerable gap between the adverse events experienced and adverse event reported; although our HCPs have fine knowledge and attitude regarding pharmacovigilance yet their practices are not upto the mark; good number of our HCPs are trained on pharmacovigilance yet their ADR reporting is low; there is a strong positive correlation between pharmacovigilance training and ADRs reporting.There is a need to develop a system for pharmacovigilanceand active measures,should be taken for making the HCP accountable for the ADRs, like remuneration, credit point system for each HCP reporting ADRs and appraisals of clinical departments reporting ADRs so as to inculcate the culture of ADRs reporting among healthcare professionals. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 648-658